2021
DOI: 10.1111/jfs.12880
|View full text |Cite
|
Sign up to set email alerts
|

Do fillers improve the physicochemical properties of antimicrobial tapioca starch edible films?

Abstract: Edible films containing natural antimicrobials, like natamycin and nisin, constitute an emerging technology that provides an additional stress factor for food preservation. However, it has been observed that edible films based only on tapioca starch present several failures, such as poor mechanical properties and low hydrophobicity. Pumpkin and oat bran are ingredients that provide multiple health benefits. In this work, it was intended to improve mechanical properties and hydrophobicity of tapioca starch edib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Similar behavior was observed by Ollé Resa et al. [ 31 ] using 1.5 wt% of OB in casting starch‐based films. On the other hand, the combination of unprocessed grains and some holes presented in the films containing the lowest concentration of bran, as morphological study shown (Figure 2B,D), could lead to the non‐modification of σ – ɛ curves behavior.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Similar behavior was observed by Ollé Resa et al. [ 31 ] using 1.5 wt% of OB in casting starch‐based films. On the other hand, the combination of unprocessed grains and some holes presented in the films containing the lowest concentration of bran, as morphological study shown (Figure 2B,D), could lead to the non‐modification of σ – ɛ curves behavior.…”
Section: Resultssupporting
confidence: 87%
“…Ollé Resa et al. [ 31 ] agreed and reported the same behavior in cassava starch films containing OB prepared by casting.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations